Transition-Metal-Free Arylation of N-Alkyl-tetrahydroisoquinolines under Oxidative Conditions: A Convenient Synthesis of C1-Arylated Tetrahydroisoquinoline Alkaloids - Singh, Kamal Nain; Kessar, Satinder V.; Singh, Paramjit; Singh, Pushpinder; Kaur, Manjot; Batra, Aanchal (Synthesis, 2014)
A simple protocol for the C1 arylation of tetrahydroisoquinolines with aryl Grignard reagents via diethyl azodicarboxylate (DEAD) mediated oxidative C–H activation under metal-free conditions has been developed. The target compounds, including some naturally occurring alkaloids, were obtained in moderate to good yields.
Keywords: arylation; tetrahydroisoquinoline; C–H activation; alkaloids; metal-free